2014
DOI: 10.1364/oe.22.025663
|View full text |Cite
|
Sign up to set email alerts
|

Reflection color filters of the three primary colors with wide viewing angles using common-thickness silicon subwavelength gratings

Abstract: We fabricated reflection color filters of the three primary colors with wide viewing angles using silicon two-dimensional subwavelength gratings on the same quartz substrate. The grating periods were 400, 340, and 300 nm for red, green, and blue filters, respectively. All of the color filters had the same grating thickness of 100 nm, which enabled simple fabrication of a color filter array. Reflected colors from the red, green, and blue filters under s-polarized white-light irradiation appeared in the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Conventional color filters, however, have used chemical pigments that are highly sensitive to constant ultraviolet (UV) light illumination, many chemicals, moisture and high temperature, all of which can cause a gradual degradation of their performance over time [1]. In order to address these challenges, many researchers have proposed and experimentally demonstrated various nanostructures that exploit optical interference effects in a thin-film configuration [2,3,4,5,6], photonic crystals [7,8,9], guided-mode resonances (GMRs) in subwavelength grating waveguides [10,11,12,13] and surface plasmon resonances (SPRs) in nanocavities patterned at the subwavelength scale [14,15,16,17,18,19,20,21,22,23,24,25,26,27]. These colors, called structural colors, have attracted substantial attention for their potential in creating distinctive colors with capabilities of achieving much improved efficiency, slim dimension, long-lasting stability and great scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional color filters, however, have used chemical pigments that are highly sensitive to constant ultraviolet (UV) light illumination, many chemicals, moisture and high temperature, all of which can cause a gradual degradation of their performance over time [1]. In order to address these challenges, many researchers have proposed and experimentally demonstrated various nanostructures that exploit optical interference effects in a thin-film configuration [2,3,4,5,6], photonic crystals [7,8,9], guided-mode resonances (GMRs) in subwavelength grating waveguides [10,11,12,13] and surface plasmon resonances (SPRs) in nanocavities patterned at the subwavelength scale [14,15,16,17,18,19,20,21,22,23,24,25,26,27]. These colors, called structural colors, have attracted substantial attention for their potential in creating distinctive colors with capabilities of achieving much improved efficiency, slim dimension, long-lasting stability and great scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple authors have demonstrated angle-independent, high-saturation, wide-gamut colors based on all-dielectric Mie metasurfaces [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. These embodiments have been based on variations of a common architecture, consisting of a 2D array of high-index (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve filter array spectroscope devices, the improvement of the filter characteristics itself is required. Although guided-mode resonant gratings are known as high-efficiency wavelength selective filters [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], they function as reflection type wavelength selective filters. Transmission type wavelength selective filters are necessary for application in filter array spectroscopes.…”
Section: Introductionmentioning
confidence: 99%